Performance Evaluation of an evolving data compression algorithm embedded into an OBD-II edge device - Signoretti, Gabriel; Silva, Marianne; Araujo, Jordy; Guedes, Luiz Afonso; Silva, Ivanovitch; Sisinni, Emiliano; Ferrari, Paolo (2020 IEEE International Workshop on Metrology for Industry 4.0 & IoT, 2020)
The new industrial revolution, known as industry 4.0, aims to create value throughout the product life cycle into all industries sectors. In the automotive industry perspective, data can be obtained throughout the life cycle of vehicles if they are appropriately instrumented with an On-Board Diagnostic scanner (OBD-II). Communications interfaces (3G/4G/LoraWan/Wi-Fi) assume essentials rules in order to relay all collected data to services in the cloud. Challenges emerge when using the Low Power, Wide-Area Network (LPWAN) protocols, as the case of LoRaWAN. This article aims to evaluate the feasibility of embedding a data compression algorithm driven by a light-weight evolving real-time approach in order to reduce the amount of data to be transmitted periodically. The proposal was embedded in a low-cost, low-power system on a chip microcontroller based on Edge OBD-II Freematics ONE+™. Results have shown the feasibility of the proposal and indicated compression rates of up to 98% without impact the primary operation of the edge device.